Some reflections on young people and types of rural territories - Dirven Eisenberg, Martine (2021)
Socio-economic indicators and access to basic services and infrastructure tend to improve when transiting from rural-distant and disperse areas toward large cities.  Rural occupied people do not usually have a “decent employment” as per ILO criteria.  Young people with more formal education and information usually have longings and expectations that cannot be fulfilled in these territories, and less so in the agricultural sector.  Cause-effect relations seem to lead to a vicious circle at the expense of rural-distant and disperse territories, except with changes in the current value-system.